Airspora over Groundnut Fields at Kalamb - Dhale2, D. S. Jadhav1*, B. Y. Patil1 and D. A. (Journal of Phytology, 2011)
In the present investigation, a groundnut (Arachis hypogea L.) crop field was selected for the aerobiological study for two years. The systematic aerobiological survey was conducted by using volumetric Tilak air sampler (Tilak and Kulkarni – 1970) for a period of two rainy crop seasons and two summer crop seasons. In the present investigation, 71 airborne fungi were isolated and identified, of the 71 spore types, 41 spore types belong to Deuteromycetes, 17 to Ascomycetes, 4 to Basidiomycetes, 3 to Phycomycetes, and 6 to other types. The percentage contribution of each spore type to the total air spora of two seasons is calculated. Key words: Airspora, Arachis hypogea, aerobiology, Tilak air sampler <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">D. S. Jadhav et al. Airspora over Groundnut Fields at Kalamb. J Phytol 2/12 (2010) 14-16.